Executive Committee Minutes 2005-08-25 - Academic Senate:::::::::
Faculty Eligible for Emeritus Status, Six days to turn in grades, Program Review Protocol revisited, Periodic Review of Administrators revision, Policy on Credit/No Credit Grading and Grade Mode change